CLAPPING, VIBRATING, POSTURAL DRAINAGE, AND EFFECTIVE COUGH AS MEASURES TO RESOLVE THE PROBLEM OF INEFFECTIVE AIRWAY CLEARANCE IN PATIENTS WITH BRONCHITIS - Pranoto, Wahyu; Bistara, Difran Nobel; Soleha, Umdatus; Winoto, Priyo Mukti Pribadi (Universitas Nahdlatul Ulama Surabaya, 2024)
Introduction: Bronchitis is characterized by excessive sputum production due to an infection in the bronchi. In patients with bronchitis, it can cause nursing problems in the form of ineffective airway clearance. Ineffective airway clearance is the inability to clear the airway which is characterized by changes in frequency, pattern, and breath sounds. Objective: The purpose of this study was to apply nursing care to patients with the application of Clapping, Vibrating, Postural Drainage, and Effective Coughing to overcome ineffective airway clearance in the Azzahra 1 Room, RSI Jemursari Surabaya. Methods: The design of this research is a case study; the time of research is 13-15 October 2022 in the Azzahra 1 Room, RSI Jemursari Surabaya. The subject used is 1 bronchitis patient (Mr. B) with a nursing diagnosis of ineffective airway clearance. The research was conducted using interviews accompanied by physical examination, observation, and documentation. Nursing care given to patients with a nursing care process approach includes assessment, nursing diagnosis, intervention, implementation, and evaluation. Results: The results of the case study found that the patient had a cough with phlegm for 2 weeks, chest pain when coughing, increased sputum production, had rhonchi, and the patient was an active smoker. Evaluation of the results of nursing care with effective Clapping, Vibrating, Postural Drainage, and Coughing for 3 days once a day showed decreased rhonchi, decreased sputum production, and patients can cough effectively independently. Conclusions: Clapping, vibrating, postural drainage and effective coughing can help clear secretions to maintain a patent airway. Nurses are expected to be able to apply effective chest and cough physiotherapy to patients so that optimal action is achieved and the patient performs independently.